THE FUNCTION OF POETRY IN THE MODERN WORLD: A CASE STUDY OF WALT WHITMAN AND AUDRE LORDE’S POEMS - Scheyer, Lauri; Abdul, Zanyar Kareem (Universitas Islam Sumatera Utara (UISU), 2022)
Lyric poetry has historically referred to a genre that we think of as brief, musical, and personal as well as subjective. This article addresses the role of lyric poetry in the modern world, and how critical analysis enables us to better appreciate the potential impact of poetry today. Specifically, we will offer brief contrastive assessments of two landmark exemplars of American poets, Walt Whitman and Audre Lorde. These two figures demonstrate some of the varied ways of the American poetry tradition. We compare Walt Whitman, a canonical white male poet from the 19th century, with an equally important 20th century African American woman poet, Audre Lorde. These American poets differ in historical periods, sex, race, and other factors, yet both uphold the conventional functions of lyric poetry and prove its continuing relevance to a global readership. The results show that as the reflection of human life, poetry could represent honesty, realism, democracy and even power.